2016
DOI: 10.1007/s13312-016-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

Childhood leprosy in an endemic area of central India

Abstract: Transmission of leprosy is still continuing in the area, and high disability and deformity rates are seen in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
1
11
1
Order By: Relevance
“…No cases of pure neurotic leprosy were seen. Patients with MB (68.18%) were more common in our study, however, this observation seems to be in contrast to the study of Sunil, et al 7 in central India.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No cases of pure neurotic leprosy were seen. Patients with MB (68.18%) were more common in our study, however, this observation seems to be in contrast to the study of Sunil, et al 7 in central India.…”
Section: Discussioncontrasting
confidence: 99%
“…In Andhra Pradesh, 4695 new cases detected, among which child cases account for 464 (9.88%), Vizianagaram is the district in Andhra Pradesh with the highest incidence of child cases, which account for 910 (19.39%). [5][6][7][8][9] A high proportion of childhood cases signifies active and recent transmission of the disease, making it a robust epidemiological indicator to assess the burden of disease in the community. Taking into consideration the above scenario the present study was undertaken in the department of DVL, Government General Hospital, Vijayawada, Andhra Pradesh, India and to evaluate the epidemiological and clinical data of patients diagnosed with leprosy less than 15 years of age, and to assess the changing trends in the post-elimination period.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, children had follow-up medical evaluations during treatment and one year after discharge, which allowed us to observe the frequency of reactions for a longer time course (in line with the characteristics and course of the disease). Some authors also reported difficulties in monitoring patients; for example, in a study in India, only 60 (10.8%) out of 551 children under 18 years of age diagnosed with leprosy had follow-up examinations during MDT 10…”
Section: Discussionmentioning
confidence: 99%
“…About 5–20% of children with leprosy will present with reaction episodes (exacerbation of inflammatory processes, either localized or systemic) at some point before, during, and/or after the end of MDT 8–10. Leprosy reactions can lead to permanent nerve damage, potentially resulting in disabilities and deformities 11,12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation